PROFITABILITAS DAN LIKUIDITAS TERHADAP AGRESIVITAS PAJAK DENGAN CAPITAL INTENSITY SEBAGAI MODERATING - Arwa El Zahra; Zuraidah (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This research endeavor seeks to delve into two pivotal aspects: initially, it seeks to assess how profitability and liquidity correlate with tax agressiveness, and secondarily, it aims to explore the mediating influence of capital intensity on the interplay between profitability, liquidity, and tax agressiveness. The study centers on the mining firms listed on the IDX, harnessing their financial records from 2014 to 2023 as the cornerstone for data analysis. Through a strategic sampling method, a subset of 10 companies was identified for the study. The analytical tools employed were multiple linear regression and multivariate regression analysis, executed via Eviews 12 software. The findings indicate that profitability has a notable impact on tax agressiveness, whereas liquidity shows a detrimental, albeit non-statistically significant, effect. Notably, capital intensity does not serve as a mitigating factor in the relationship between profitability, liquidity, and tax agressiveness.